2013
DOI: 10.1002/jgrb.50096
|View full text |Cite
|
Sign up to set email alerts
|

Understanding progressive‐arc‐ and strike‐slip‐related rotations in curve‐shaped orogenic belts: The case of the Olevano‐Antrodoco‐Sibillini thrust (Northern Apennines, Italy)

Abstract: We report on a paleomagnetic study of the southern sector of the Olevano‐Antrodoco‐Sibillini (OAS) thrust front, which corresponds to the southern limb of the Northern Apennines (Italy) orogenic salient. A lively debate has developed regarding the oroclinal/progressive‐arc versus non‐rotational nature of the OAS, which has been alternatively interpreted as a dextral strike‐slip fault, dextral transpressive fault, or frontal to oblique ramp that reactivated pre‐existing Jurassic normal faults. Here, we document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 97 publications
1
13
0
Order By: Relevance
“…First, we calculated σ 3 and σ 1. Our field data and previously published data [ Coli , ; Cavinato et al ., ; Calamita and Deiana , ; Calamita et al ., ; Corrado , ; Turtù et al ., ] indicated a compressional regime during the slip of the Olevano–Antrodoco thrust fault. This implies a horizontal σ 1 oriented SW‐NE and a vertical σ 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we calculated σ 3 and σ 1. Our field data and previously published data [ Coli , ; Cavinato et al ., ; Calamita and Deiana , ; Calamita et al ., ; Corrado , ; Turtù et al ., ] indicated a compressional regime during the slip of the Olevano–Antrodoco thrust fault. This implies a horizontal σ 1 oriented SW‐NE and a vertical σ 3.…”
Section: Discussionmentioning
confidence: 99%
“…The Olevano–Antrodoco is an out‐of‐sequence thrust fault [ Cipollari et al ., ] characterized by multiphase prevalently dextral transpressional kinematics [ Coli , ; Cavinato et al ., ; Calamita and Deiana , ; Calamita et al ., ; Corrado , ; Turtù et al ., ], although evidence for strike‐slip kinematics on other fault segments oriented N‐S in Central Apennines are reported by some authors [ Castellarin et al ., ; Cello et al ., ; Cello and Mazzoli , ].…”
Section: Geological Settingmentioning
confidence: 99%
“…These include the so-called 41° Parallel Line, which divides the northern and southern Tyrrhenian Sea basins, the Tindari-Letojanni fault systems and others (e.g. Serri 1990;Bruno et al 2000;Rosenbaum et al 2008;Turtù et al 2013). It has been suggested that tear-off fractures of the Adriatic-Ionian subducted slab occur along some of these faults.…”
Section: Summary Of the Geodynamic Evolution Of The Tyrrhenian Sea Areamentioning
confidence: 99%
“…Studies from arcs of 10-100 km of amplitude have documented different behaviours: there are minor arcs characterized by CCW and CW rotations along the limbs (Gran Sasso Range (Satolli et al 2005)), block rotations due to strike-slip faults (e.g. Central Apennines (Mattei et al 1995) and Olevano-Antrodoco sibilini thrust (Turtù et al 2013)) and small homogeneous CW-rotated structures (e.g. Mount Maiella (Jackson, 1990) and Mount Greco -Mount Genzana (Marton & D'Andrea, 1992)).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the development of the Northern Apennines progressive arc was influenced by the architecture of the Adria palaeomargin (Calamita et al 2012). The system has a component of primary and progressive arc development: its primary curvature was accentuated during orogenesis by CCW and CW tectonic rotations in its northern and southern limbs, respectively Turtù et al 2013). The importance of inversion tectonics has also been shown through palaeomagnetism in minor arcs, as in the case of the Gran Sasso range (central Apennines), where the Adria palaeomargin played the role of an indenter causing strong rotations in its apex (Satolli et al 2005).…”
Section: Introductionmentioning
confidence: 99%